Rights of children in criminal proceedings: a comparative analysis on the compatibility of the Malaysian juvenile justice system with the standards of the convention on rights of children (CRC) - Aminuddin Mustaffa
The rights of children in conflict with the law has always been a central subject of juvenile justice which attracts an intense academic, political and media interest and debate. In this respect, the United Nations Convention on Rights of Children (CRC), which was adopted on zo" November 1989, has laid down international standards and legal framework on rights of children under juvenile justice. The CRC's standards on this matter have erved as a useful guideline and benchmark to state parties in determining and assessing the rights of children in criminal proceedings. As a country that has ratified the CRC in 1995, Malaysia is duty-bo to strive toward full implementation of the requirements of the CRC. This study will specifically focus on examining the legal rights of children in criminal proceedings under both the CRC's standards and the Malaysian juvenile justice system. Using the CRC's tandards as a guideline and a benchmark, the study aims to asses the rights of children in riminal proceedings under the current Malaysian juvenile justice system. The study will attempt to critically and comparatively analyze to what extent the Malaysian juvenile justice system on the rights of children in criminal proceedings measure up with the CRC's standards. The study concludes that legal reform of current legal framework and policy is necessary to improve and strengthen rights of children in criminal proceedings under Malaysian juvenile justice system. Aiming towards full implementation of the CRC's standards on this aspect, the study provides recommendations and suggestions to be considered in respect of certain imprecision and loopholes in laws as well as policy under the existing Malaysian juvenile justice system.